Peran konsep diri siswa dalam membangun perilaku asertif - Alifiah, Rizqi; Febrieta, Ditta (JURNAL PENDIDIKAN DAN SAINS, 2024)
In principle, today's students have the ability to express opinions, dare to ask questions and provide critical opinions, but there are also students who, when giving opinions, prefer to remain silent because of various arguments such as: embarrassment, fear of incompetence, fear of being laughed at, and so on. Assertive behavior is the behavior of someone who is able to act according to their own wishes, defend themselves without feeling nervous, express their feelings, exercise their personal rights by saying what they are, without being hindered, and not exceeding other people's boundaries. Assertive behavior can be influenced by several factors, one of which is self-concept. The aim of this research is to understand the influence of self-concept on assertive behavior among students in Jakarta. The respondents of this research involved 132 students in Jakarta. This research uses the Simple Linear Regression Analysis method and finds the influence of self-concept related to assertive behavior. The results show that self-concept has an influence of 31.6%. These results also show that assertive behavior is higher for men than women, but there are no differences in self-concept based on gender.